2003
DOI: 10.1080/10803548.2003.11076577
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Deep Vein Thrombosis in VDU Work

Abstract: This paper introduces preventive measures against Deep Vein Thrombosis (DVT) during Visual Display Units (VDU) work. Four experiments were conducted in order to address this issue. The effectiveness of the preventative measures was evaluated by measuring foot swelling. The results indicated that the following 3 methods would be particularly effective: (a) occasionally adopting a reclining posture with a footrest, (b) 10-min walking every 50-60 min of VDU work, and (3) stretching. In addition we predicted that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Swelling of the feet is often found in people who work in front of a VDT for a prolonged period, indicating poor peripheral circulation. 24) The present study suggests that ingestion of NKCP ® increased the skin surface temperature, thus improving peripheral blood flow in the shoulders and neck as well as in the lower extremities. Thus, NKCP ® may prevent swelling of the feet in addition to improving neck and shoulder stiffness.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Swelling of the feet is often found in people who work in front of a VDT for a prolonged period, indicating poor peripheral circulation. 24) The present study suggests that ingestion of NKCP ® increased the skin surface temperature, thus improving peripheral blood flow in the shoulders and neck as well as in the lower extremities. Thus, NKCP ® may prevent swelling of the feet in addition to improving neck and shoulder stiffness.…”
Section: Discussionsupporting
confidence: 50%
“…Skin surface temperature and blood flow are also used to assess neck and shoulder pain and dysfunction. [19][20][21][22][23] In order to assess blood flow near the shoulders and neck, the current study also measured skin surface temperature and blood flow. NKCP ® did not increase blood flow in the shoulders and neck, but it increased skin surface temperature in those areas.…”
Section: Discussionmentioning
confidence: 99%
“…Mitsuya et al 57 have suggested to sit in a reclining posture and occasionally use a footrest, stretch the legs, and walk 10 min during breaks. However, studies to assess the effectiveness of such recommendations are still needed.…”
Section: Venous Thromboembolismmentioning
confidence: 99%